The Difference that Language Makes: A Response to Paul Giles’ “World Literature and International American Studies: Convergence, Divergence, and Contest” - Giorcelli, Cristina (Review of International American Studies, 2017)
Cristina Giorcelli Facolta' di Lettere e Filosofia Università degli Studi Roma Tre The Difference that Language Makes: A Response to Paul Giles’ “World Literature and International American Studies: Convergence, Divergence, and Contest” A Response to Paul Giles’ “World Literature and International American Studies: Convergence, Divergence, and Contest.” (in the present issue). Keywords: formation of International American Studies, World Literatures, academic politics